Reterritorialization and aesthetic transformations: the case of Tony Harrison's Phaedra Britannica and The Misanthrope. (4th July 2018) - Ploix, Cédric
ABSTRACT: This article analyses the impact of reterritorialization on classics of the stage. After reflecting on some particularities of classical works, the article focuses on The Misanthrope and Phaedra Britannica by British poet Tony Harrison, the first and rare successes of Molière, and particularly Racine on the Anglo-Saxon stage. It compares the main aesthetic features of Molière's and Racine's works with the modernizations operated by Harrison, and comments on the relevance of the historical and geographical transfer as a domestication strategy. While reterritorialization strategically includes the spectator, it does so not without a major impact on certain characteristics of seventeenth-century French theatre. The fact that the plays have a strong aesthetic identity makes the transformations striking. Indeed, what makes up the identity of classical French theatre, namely the unity of action, characterization, passions and, more generally, the nature of comedy and tragedy, is transformed by reterritorialization. Also dependent on reterritorialization, dramatic language, notably rhythm, semantics and versification, is metamorphosed. These two case studies on the impact of historical and geographical transfer shed light on the points of disparity between classical French theatre and expectations of the modern English audience, and help to address other reterritorialized adaptations of classics.